Gouda cheese with different coagulants and types of milk: physicochemical, biochemical, microbiological, and sensory properties - Mohsin, Aliah Zannierah; Hui Ci, Ngu; Ismail, Anwar Ridhwan; Marzlan, Anis Asyila; Abd Rahim, Muhamad Hafiz; Meor Hussin, Anis Shobirin (Springer, 2023)
The type of coagulant used in cheese production is a significant contributor to proteolysis during ripening. The common application of calf rennet faces restrictions due to ethical, cultural, and dietary concerns. This research determined the physicochemical, biochemical, microbiological, and sensory properties of Gouda cheese using fermentation-produced chymosin (FPC) and microbial coagulant (MC) produced from cow and buffalo milk. Buffalo milk was chosen based on its high-fat content and underutilised application in the cheese industry. Gouda cheese from buffalo milk with FPC has the highest fat (38.5%), moisture (38.77%), cheese production yield (12.88%), as well as the highest monounsaturated and polyunsaturated fatty acids. No yeast or mould are detected in Gouda cheese from buffalo milk FPC or buffalo milk MC. Gouda cheese from buffalo milk FPC has a significantly lower total plate count and lactic acid bacteria count. Based on its overall acceptability score, Gouda cheese from buffalo milk FPC can be a good alternative to traditional Gouda cheese from cow milk.